2022
DOI: 10.1177/20503121221085109
|View full text |Cite
|
Sign up to set email alerts
|

Musculoskeletal disorders among the population in Northwest Ethiopia

Abstract: Objective: This study aimed to assess the magnitude and patterns of chronic musculoskeletal disorders among the population in East Gojjam zone, Northwest Ethiopia. Methods: A community-based cross-sectional study with 846 recruited study participants was done using a multistage sampling technique in conjunction with a simple and systematic random sampling technique. Face-to-face interviews, physical examinations, a semi-structured questionnaire adapted from the Community Oriented Program for Control of Rheumat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 52 publications
0
3
1
Order By: Relevance
“…This finding indicated that the overall prevalence of self-reported MSDs symptoms among water-carrying women was 72.5% which was consistent with the study conducted in Brazil (72.7%) ( 23 ). However, this result was greater than that of studies done in Ethiopia with healthcare professionals 64.2% ( 24 ), 40.1% ( 25 ), hairdressers (47.5%) ( 26 ), computer users (bankers) (58.8%) ( 27 ), and healthcare providers (44.2%) ( 28 ), diabetic patients (23.29%) ( 29 ), barber workers (55.7%) ( 30 ), and cleaners (52.3%) ( 31 ).…”
Section: Discussioncontrasting
confidence: 61%
“…This finding indicated that the overall prevalence of self-reported MSDs symptoms among water-carrying women was 72.5% which was consistent with the study conducted in Brazil (72.7%) ( 23 ). However, this result was greater than that of studies done in Ethiopia with healthcare professionals 64.2% ( 24 ), 40.1% ( 25 ), hairdressers (47.5%) ( 26 ), computer users (bankers) (58.8%) ( 27 ), and healthcare providers (44.2%) ( 28 ), diabetic patients (23.29%) ( 29 ), barber workers (55.7%) ( 30 ), and cleaners (52.3%) ( 31 ).…”
Section: Discussioncontrasting
confidence: 61%
“…The NMQ has also been validated and proven to be reliable in a variety of languages with acceptable psychometric properties 44 45. In Ethiopia, previous studies have made extensive use of the NMQ to investigate the public health problems associated with disorders in different populations 28 46 47…”
Section: Methodsmentioning
confidence: 99%
“…The NMQ has been validated and proven to be reliable in a variety of languages with acceptable psychometric properties [49,50]. In Ethiopia, previous studies have made extensive use of the NMQ to investigate the public health problems associated with disorders in different populations [5,28,51]. The questionnaire's third section contains information used to assess behavioral and psychosocial factors such as cigarette BMI (kg/m 2 ), physical activity (yes/no), smoking (yes/no), alcohol consumption (yes/no), chewing khat (yes/no), history of chronic illness (yes/no), perceived severity and disability of musculoskeletal pains, as well as perceived job satisfaction and perceived job stress.…”
Section: Data Collection Tools and Proceduresmentioning
confidence: 99%